Frequency of atrial thrombus formation in patients with atrial fibrillation under treatment with non-vitamin K oral anticoagulants in comparison to vitamin K antagonists: a systematic review and meta-analysis - Stefan Reers; Georg Karanatsios; Matthias Borowski; Michael Kellner; Michael Reppel; Johannes Waltenberger (European Journal of Medical Research, 2018)
Abstract Background To assess the frequency of left atrium/left atrial appendage (LA/LAA) thrombus under treatment with non-vitamin K oral anticoagulants (NOACs) in comparison with vitamin K antagonists (VKAs) in patients with non-valvular atrial fibrillation (AF). Methods PubMed, Web of Science™, EMBASE and the Cochrane Library databases were searched for studies comparing NOACs with VKAs in AF patients who underwent diagnostic transoesophageal echocardiography (TEE). Results A total of four trials were considered eligible and were included in the meta-analysis. Four RCTs comprising n = 2397 AF patients (NOACs: n = 1412, VKAs: n = 985) were included in the meta-analysis. The frequency of LA/LAA thrombus formation under treatment with NOACs was similar to VKAs [odds ratio (OR) 1.14, 95% confidence intervals (95% CIs) 0.97–1.65, p = 0.48]. Both treatment groups revealed an approximately 5% frequency of thrombus formation, although a precise calculation is not possible due to Simpson paradox. Indications of heterogeneity between the included trials were not found (χ 2 test p = 0.99, I 2 = 0%). Conclusions The findings of this meta-analysis suggest that NOACs are similar to VKAs regarding the frequency of LA/LAA thrombus in patients with AF. An unknown number of patients in the original studies did not receive sufficient anticoagulation for at least 3 weeks prior to TEE examination, and therefore the present results should be interpreted with caution. Systematic review registration—http://www.crd.york.ac.uk/PROSPERO. Unique identifier: PROSPERO CRD42017059293.